The benefit, risk and factors influencing of dietary supplement intake among adult/Nur Adlina Zurdi & Nur Hamizah Ahmad - Zurdi, Nur Adlina; Ahmad, Nur Hamizah (Faculty of Hotel and Tourism, 2016)
Dietary supplements are one of the biggest trends in the healthcare industry whereby the consumers are now taking charge of their health and they are seeking alternative medicine. This also may include ingredients such as vitamin, minerals, amino acids, natural plant substances and animal origin, substances with nutritional or physiological function. Basically, the products are used for many purposes such as to promote the overall health and energy, provide immune system support, thin out the risks of sickness and age-linked conditions, and improve performance in athletic and mental actions as well as to sustain thehealing process during illness and disease. These aims to identify the influence factors on dietary supplements consumptions among adult and also discuss about the benefits and risk of dietary supplements intake among adults.This study has been conducted by using a conceptual approach where all the information was gathered from previous research. The result revealed benefit and risk is the main factor to contribute the main factor to contribute the consumption of dietary supplements